OBESITY DISEASE - NON-SURGICAL TREATMENT METHODS - A LITERATURE REVIEW - Zuzanna Rabczak; Marcin Narloch; Jakub Kamiński; Jan Tomczyk; Aleksandra Żywicka; Oskar Sienkiel; Kamila Mozga; Mateusz Jasiński; Michał Szalach; Stanisław Kasprzak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Obesity, a global health crisis, is a leading risk factor for chronic diseases like diabetes and cardiovascular disease. Its prevalence has more than doubled since 1990, straining healthcare systems. Management involves primary prevention (lifestyle interventions), secondary prevention (early detection and treatment), and tertiary prevention (managing established obesity via lifestyle changes, pharmacotherapy, or bariatric surgery). This review focuses on non-invasive treatment methods for obesity. Materials and methods: This review was conducted using PubMed and Google Scholar databases, focusing on recent systematic reviews, meta-analyses, and original research on non-surgical obesity treatments. Keywords included obesity, diet, exercise, pharmacotherapy, and education. Results: Recent findings suggest that combining reduced calorie intake with limited carbohydrate consumption can lead to more effective weight loss. Diets high in protein, particularly those containing whey, are beneficial for maintaining muscle mass during weight reduction. Medications such as GLP-1 receptor agonists support weight loss and metabolic health. Regular physical activity enhances fat loss and cardiovascular performance. Additionally, patient-focused strategies are essential for improving adherence and ensuring long-term success in obesity treatment. Conclusions: Effective obesity treatment requires combining personalized nutrition plan, physical activity, and medications. Prioritizing muscle preservation, protein intake, patient education, and stigma reduction enhances adherence and supports long-term weight and metabolic health outcomes.